A Production Monitoring Scheme For Continuous Mining Sections - Jeffery L. Kohler (Society for Mining, Metallurgy & Exploration, 1988)
A method of monitoring production, information, i.e., raw tonnage and machine state, from each working section has been developed. The method is based on the sensing of electrical parameters in each section load center, and the reporting of this information through the existing mine-wide monitoring system. A decision-theoretic type of pattern classification technique has been used to define the machine states. The basis of the method is presented in this paper, along with a proposed hardware and software implementation scheme. Information issues central to the development and use of the proposed production monitoring system are also discussed.